Accounts on the aphid fauna of North-Eastern ltaly (Bollettino di zoologia agraria e bachicoltura, 2024)
The aphid fauna of the North-Eastern territory of the Italian peninsula (including the three administrative regions Trentino-Alto Adige, Veneto and Friuli-Venezia Giulia) is presently composed of 408 taxa, of which 265 were detected in the first regìon, 130 in the second and 257 in the third region. Nevertheless, on the basis of the very wide range of floristic associations and ecosystems in the territory, the aphid fauna composition is expected to be more numerous than that presently known. The aphid taxa detected so far in the territory are inclusive of thirty-three species or subspecies not yet known for the Italian aphid fauna; short ecological and taxonomic accounts are given on each of these unrecorded aphids.
Keywords: Aphid fauna; North-Eastern Italy